Concentração de melatonina no leite humano, qualidade do sono e saúde mental materna: estudo transversal - Oliveira, Flávia Silva e (2024)
Oliveira FS. Melatonin Concentration in Human Milk, Sleep Quality, and Maternal Mental Health: Cross-Sectional Study [thesis]. Goiânia: Faculdade de Enfermagem/UFG; 2023. p. 196. INTRODUCTION: Melatonin is an endogenous hormone present in human milk and plays a crucial role in regulating the circadian rhythm. Its association with mood disorders and sleep disturbances during the postpartum period is still underexplored. OBJECTIVE: To investigate the association between melatonin concentration in human milk and the quality of sleep, presence of depressive symptoms, anxiety, and maternal stress in the postpartum period. METHODOLOGY: A cross-sectional study was conducted with 84 women in the postpartum period in the public healthcare system. Data collection took place between June 2021 and December 2022, with participants approached in the postpartum ward of the maternity unit. Human milk samples were collected through manual expression between 6 a.m. and 9 a.m. on day 14 postpartum. The samples were stored at -80°C and analyzed using an enzymelinked immunosorbent assay (ELISA). Sociodemographic, obstetric, and neonatal data were collected, and questionnaires on postpartum depression (Edinburgh Postnatal Depression Scale, EPDS), anxiety, stress (Depression, Anxiety, and Stress Scale, DASS-21), and sleep quality (Pittsburgh Sleep Quality Index, PSQI) were administered. Statistical analysis included measures of central tendency and dispersion, bivariate Poisson regression, and multivariate modeling, with p < 0.05 considered statistically significant. RESULTS: The median melatonin concentration was 4.90 pg/ml (Q1: 2.78; Q3: 13.61). Depressive symptoms were reported by 22.6% of the women, anxiety symptoms by 39.3%, stress symptoms by 38.1%, and sleep disturbances by 63.1%. In the multivariate analysis, associations were found between melatonin concentration ≤ 4.90 pg/ml, planned pregnancy (RP: 1.21; 95% CI: 1.04 - 1.42; p = 0.015), and anxiety symptoms (RP: 1.18; 95% CI: 1.02 - 1.37; p = 0.030). Postpartum depressive symptoms were associated with paid employment (RP: 2.58; 95% CI: 1.20 - 5.52; p = 0.015), stress symptoms (RP: 3.84; 95% CI: 1.04 - 14.21; p = 0.044), and sleep disturbances (RP: 3.07; 95% CI: 1.13 - 8.33; p = 0.027). Significant associations were also observed between stress symptoms and unplanned pregnancy (RP: 3.06; 95% CI: 1.16 - 8.12; p = 0.024), anxiety symptoms (RP: 3.06; 95% CI: 2.06 19 - 7.80; p < 0.001), and postpartum depressive symptoms (RP: 1.93; 95% CI: 1.12 - 3.33; p = 0.017). For anxiety symptoms, an association was found with stress symptoms (RP: 1.19; 95% CI: 1.53 - 7.26; p = 0.002) and newborn weight (RP: 1.00; 95% CI: 1.00 - 1.01; p = 0.004). The presence of sleep disturbances was associated with the number of people in the household (RP: 0.71; 95% CI: 0.54 - 0.94; p = 0.015). CONCLUSION: Melatonin concentration in human milk was higher than the daytime levels reported in the literature. The association between melatonin and anxiety symptoms emphasizes the importance of identifying modifiable factors during the perinatal period. The relationship between mood disorders and sleep disturbances suggests a simultaneous or precedence interaction between these conditions.